GENDER EQUALITY IN RELIGIOUS COURT DECISIONS: A STUDY OF ALIMONY AND THE STATUS OF MAFQUD HUSBANDS FROM AN ISLAMIC FAMILY LAW PERSPECTIVE - Jamil, Nur Cahya; Alam, Syariful (LPPM STIH Putri Maharaja, 2025)
The rising rate of female-initiated divorce in Indonesia highlights women's vulnerability due to neglected fundamental rights, specifically alimony, and the prevalence of mafqud (missing) husbands. This situation forces wives into a dilemma of legal uncertainty and structural economic burdens. This study aims to analyse the implementation of gender equality principles in Religious Court decisions concerning the protection of wives' economic rights in cases involving mafqud (missing) husbands, while also examining the consistency of legal application in judicial practice. The research employs a normative-juridical method, using statutory, conceptual, and case-study approaches, analysing three specific Religious Court decisions: PA Kendal (2023), PA Kaimana (2021), and PA Merauke (2011). The results indicate significant legal disparities in the adjudication of similar cases. Some courts maintain a formalistic approach that merely provides legal certainty regarding divorce status without restoring the wife's economic rights. Conversely, other courts have begun adopting a substantive justice approach by granting iddah maintenance (nafkah iddah) and consolatory gifts (mut’ah). This inconsistency suggests that legal protection for women remains a potential